Some problems of the legal organization of the federal state quarantine phytosanitary control (supervision) (Гуманитарные и юридические исследования)
Introduction. Proper organization of state quarantine phytosanitary control (supervision) is a factor affecting the state of economic and food security, since it involves the application of measures aimed at preventing the penetration and spread of biological organisms harmful to the crop industry. The legal norms regulating the organization of state phytosanitary control (supervision) form one of the most important legal institutions in the structure of administrative and legal regulation of the agro-industrial complex.Materials and Methods. The study was conducted using general scientific methodology (analysis, synthesis, dialectical and system-structural methods), as well as the formal legal method. For this purpose, the necessary regulatory and legal framework was used, and the scientific argumentation of the formulated ideas was based on the study of theoretical sources, in which topical issues of the legal organization of public administration, control and supervisory activities and plant quarantine were considered.Analysis. The main directions of the analysis are the problems of organizing and implementing state quarantine phytosanitary control (supervision) with a statement of the circumstances that prevent the normal implementation of control and supervisory measures.Results. The expediency of legislative registration of the monitoring of the quarantine phytosanitary condition of the territory of the Russian Federation and the measures of administrative coercion applied during its implementation in the form of an integral part of the state quarantine phytosanitary control (supervision) has been established. Further development of its regulatory and legal regulation may be associated with the unification of terminology affecting such measures as inspection and inspection. The conclusion is formulated about the need to take organizational and legal measures to increase the level of material and technical security of the relevant bodies and officials.